Cross-sectional study for derivation of a cut-off value for identification of an early versus delayed diagnosis of endometriosis based on analytical and descriptive research methods - Iris Brandes; Katja Kleine-Budde; Nicole Heinze; Sebastian Binder; Constanze Klug; Cordula Schippert; Andreas D. Ebert; Gülden Halis (BMC, 2022)
Abstract Background Endometriosis is a benign, hormone-dependent, chronic inflammatory gynecological disease accompanied by cyclic and acyclic pelvic pain and other complaints. The long lists of research recommendations in the AWMF guideline (Burghaus et al., Geburtshilfe Frauenheilkd 81:422-46, 2021) and ESHRE Endometriosis Guideline (ESHRE Endometriosis Guideline Development Group, Endometriosis: Guideline of European Society of Human Reproduction and Embryology, 2022) show that there is still a great need for research in all aspects of the disease. Diagnostic delay, defined as the mean time between symptom onset and confirmed diagnosis, is a particular problem associated with endometriosis. Some quantitative and qualitative studies have investigated possible reasons for this. A range of physician-related (Dixon et al., Br J Gen Pract 71:e668-e676, 2021; van der Zanden and Nap, Reprod Biomed Online 32:527-31, 2016) and patient-related factors (Sayer-Jones and Sherman, Health Psychol Behav Med 9:456-79, 2021) as well as stigmatization of the topic of menstruation by society have been identified (Kruckenberg, Frauenarzt 59:2-5, 2018; Seear, Soc Sci Med 69:1220-7, 2009). The consequences of the disease being diagnosed late (or too late) on the course of disease, the quality of life and the costs of the disease have already been documented in studies (Sims Int J Environ Res Public Health 18(15):8210, 2021; Surrey Adv Ther 37:1087-99, 2020). However, a systematically derived cut-off value that clearly distinguishes between short and long delay is still lacking. Therefore, the aim of our study was to derive a threshold value for the definition of a target corridor for endometriosis diagnosis based on descriptive and analytical methods. Methods Since our review of the rather sparse publications on diagnostic delay did not yield satisfactory results, we used descriptive statistics and location parameters to calculate a cut-off value for German population data from the EndoCost study. Statistical methods were used for correlation analysis of shortDD versus longDD (correlation analysis and logistic regression) and group membership (discriminant analysis). Results Five years was identified as the cut-off value that significantly differentiated between shortDD and longDD based on various disease-related variables. This suggests that endometriosis should be definitively diagnosed within less than five years to minimize the risk of an unfavorable course of the disease. Conclusion Our findings confirmed that an early onset of endometriosis-related symptoms is the most important risk factor for a long diagnostic delay. Consequently, adolescent females should receive increased attention as an especially vulnerable group. Evidently, there is an urgent need to develop adequate concepts to improve the endometriosis education and care among this target group.